Discovery of a Potent Highly Biased MOR Partial Agonist among Diastereomeric C9-Hydroxyalkyl-5-phenylmorphans - Lutz, Joshua A.; Sulima, Agnieszka; Gutman, Eugene S.; Bow, Eric W.; Luo, Dan; Kaska, Sophia; Prisinzano, Thomas E.; Paronis, Carol A.; Bergman, Jack; Imler, Gregory H.; Kerr, Andrew T.; Jacobson, Arthur E.; et al. (Molecules (Basel, Switzerland), 2023)
All possible diastereomeric C9-hydroxymethyl-, hydroxyethyl-, and hydroxypropyl-substituted 5-phenylmorphans were synthesized to explore the three-dimensional space around the C9 substituent in our search for potent MOR partial agonists. These compounds were designed to lessen the lipophilicity observed with their C9-alkenyl substituted relatives. Many of the 12 diastereomers that were obtained were found to have nanomolar or subnanomolar potency in the forskolin-induced cAMP accumulation assay. Almost all these potent compounds were fully efficacious, and three of those chosen for in vivo evaluation, 15, 21, and 36, were all extremely G-protein biased; none of the three compounds recruited beta-arrestin2. Only one of the 12 diastereomers, 21 (3-((1S,5R,9R)-9-(2-hydroxyethyl)-2-phenethyl-2-azabicyclo[3.3.1]nonan-5-yl)phenol), was a MOR partial agonist with good, but not full, efficacy (Emax = 85%) and subnanomolar potency (EC50 = 0.91 nM) in the cAMP assay. It did not have any KOR agonist activity. This compound was unlike morphine in that it had a limited ventilatory effect in vivo. The activity of 21 could be related to one or more of three well-known theories that attempt to predict a dissociation of the desired analgesia from the undesirable opioid-like side-effects associated with clinically used opioids. In accordance with the theories, 21 was a potent MOR partial agonist, it was highly G-protein biased and did not attract beta-arrestin2, and it was found to have both MOR and DOR agonist activity. All the other diastereomers that were synthesized were either much less potent than 21 or had either too little or too much efficacy for our purposes. It was also noted that a C9-methoxymethyl compound with 1R,5S,9R stereochemistry (41) was more potent than the comparable C9-hydroxymethyl compound 11 (EC50 = 0.65 nM for 41 vs. 2.05 nM for 11). Both 41 and 11 were fully efficacious.